Effectiveness Of an Educational Package On “Prevention Of Substance Abuse on Knowledge, Attitude And Practice Of Girls In Selected Colleges Of Delhi - Jyoti Singh; Santosh Mehta; R. G. Mathur (Indian Journal of Psychiatric Nursing)
A study to determine the extent of substance use and to assess the effectiveness of an educational package on prevention of substance use in terms of knowledge, attitude and practice of girls in selected colleges of Delhi. The research design adopted was pre experimental one group pre test post test design. Data was collected from 200 students of Delhi University with the help of structured knowledge questionnaire, attitude scale and practice checklist. The obtained data was analysed and interpreted using descriptive and inferential statistics in terms of frequency, percentage, mean, median, standard deviation and “t value”. Findings suggested that 33.5% girls used tobacco, and 45.5% girls used alcohol.